Recomendaciones para el manejo en el domicilio de los pacientes adultos, pertenecientes al área urbana, con diagnóstico de covid-19 leve basadas en un consenso de expertos (2021)
Objective. Generate recommendations for home management of adult patients, in urban areas, with a COVID-19 level diagnosis based on a consensus of experts. Method. This qualitative study comprised the consensus of experts through the Delphi technique, where the recommendations found in the literature search were evaluated according to 13 guiding questions. Results. 9 experts in different areas participated and evaluated 107 recommendations to finally reach a consensus of 76 in two rounds of discussion. Conclusion. The Delphi technique facilitates quickly obtaining consensus on emerging issues and priorities for Public Health, such as the COVID-19 pandemic. The success of its application consists in the consideration of all the relevant aspects for the construction of the guiding questions, aspects that can be provided by the different actors of the health system. In addition, the recommendations must include relevant aspects for the prevention of contagion within the family nucleus derived from patient care, taking into account the scope of the caregivers to avoid their overload and identifying health-providing institutions and insurers as allies in rapid response to warning signs and monitoring of your health status.